The equation 8x² - 48x = -104 rewritten in the form x² + (-6x) = -13.
By completing the square we have x² - 6x + 9 = -13 + 9.
The equation 8x² - 48x = -104 is a quadratic equation whose general form is expressed as ax² + bx + c. Writing the given equation so that a = 1 implies we reduce the coefficient of x² to become 1, this is done as follows:
We divide the equation 8x² - 48x = -104 through by 8;
8x²/8 - 48x/8 = -104/
x² - 6x = -13
For it to be in the form: x² + __x = __, we rewrite as: x² + (-6)x = -13.
By completing the square, we find a number that will complete the left hand side to become a square and also add it to both sides of the simplified equation.
x² - 6x + 9 = (x - 3)² so
x² - 6x + 9 = -13 + 9.
Therefore, the equation can be rewritten in the form x² + (-6x) = -13, and by completing the square it is expressed as x² - 6x + 9 = -13 + 9.